Lactoferrin from Milk: Nutraceutical and Pharmacological Properties - Francesco Giansanti; Gloria Panella; Loris Leboffe; Giovanni Antonini (MDPI AG, 2016)
Lactoferrin is an iron-binding protein present in large quantities in colostrum and in breast milk, in external secretions and in polymorphonuclear leukocytes. Lactoferrin's main function is non-immune protection. Among several protective activities shown by lactoferrin, those displayed by orally administered lactoferrin are: (i) antimicrobial activity, which has been presumed due to iron deprivation, but more recently attributed also to a specific interaction with the bacterial cell wall and extended to viruses and parasites; (ii) immunomodulatory activity, with a direct effect on the development of the immune system in the newborn, together with a specific antinflammatory effects; (iii) a more recently discovered anticancer activity. It is worth noting that most of the protective activities of lactoferrin have been found, sometimes to a greater extent, also in peptides derived from limited proteolysis of lactoferrin that could be generated after lactoferrin ingestion. Lactoferrin could therefore be considered an ideal nutraceutic product because of its relatively cheap production from bovine milk and of its widely recognized tolerance after ingestion, along with its well demonstrated protective activities. The most important protective activities shown by orally administered bovine lactoferrin are reviewed in this article.